Student loan reforms for German higher education: Financing tuition fees - Bruce Chapman; Mathias Sinning (Institute for the Study of Labor (IZA), 2011)
It is generally agreed that the funding base for German universities is inadequate and perhaps the time has come for serious consideration of the imposition of non-trivial tuition charges. Against this background, this paper compares conventional and income contingent loans for financing tuition fees at German universities. With the use of unconditional age-income quantile regression approaches our analysis considers two critical aspects of the loan debate: the size of repayment burdens associated with normal mortgage-style loans, and the time structure of revenue to the government from a hypothetical income contingent loan scheme. It is found tuition fees at German universities could increase considerably with the use of an income contingent loan system based on current policy approaches used in Australia, England and New Zealand.
urn:nbn:de:101:1-201104133344
Keywords: H52; I22; I28; 330; educational finance; student financial aid; state and federal aid; government expenditures on education; Studienfinanzierung; Hochschulpolitik; Öffentliche Bildungsausgaben; Teilstaat; Deutschland